PERBANDINGAN PEMECAHAN MASALAH TRANSPORTASI ANTARA METODE NORTHWEST-CORNER RULE DAN STEPPING-STONE METHOD DENGAN ASSIGNMENT METHOD - Rudy Santosa Sudirga (Business Management Journal, 2017)
The famous methods to determine and solve transportation problem are the Northwest-corner rule/method and the Stepping-stone Method. In the Northwest-Corner Rule, the largest possible allocation is made to the cell in the upper left-hand corner of the tableau, followerd by allocations to adjacent feasible cells; while the Stepping-Stone Method is an iterative technique for moving from an initial feasible solution to an optimum feasible solution which continues untul the optimum solution is reached. However, inn some cases, sometimes we have been facing some difficulties to solve transportation problem with these two methods, therefore we intoduce the Assignment Method, which is simpler and faster in solving the transportation problem by reducing the numbers (cost) in the table/tableau until a series of zeros is found, or zero opportunity costs, which means that will reach the optimum cost allocations. Once reach the optimum cost allocations, the next step is to allocate each source or supply according to some points of demand (destinations). Assignment Method is a specialized form of optimization linear programming model that attempts to assign limited capacitiy to various demand points in a way that minimizes costs.Keywords :assignment method, linear programming, lowest opportunity cost, minimize time required